Hundred Years of the Russian Revolution
XXII, 307 p.
Keywords: “The editors have assembled a fine group of scholars, offering diverse perspectives on the legacies of the Russian Revolution of 1917 and its far reaching impact on the political, economic and social structures around the world.” ----- Devendra Kaushik, Noted scholar on Eurasian affairs, Senior Professor ( Retd), JNU, India “The editors of the volume, deserve credit for bringing together varying perspectives that facilitate a wider and clearer understanding of those “ten days that shook the world” and continue to influence the course of global history and politics.” -------------- Tatiana Shaumyan, Head, Centre for Indian Studies, Institute of Oriental Studies, Russian Academy of Sciences, Moscow “The most distinguishing feature of this volume on the Russian Revolution is its search for diverse methods of historical interpretation and the re-evaluation of the events of 1917 in the light of the contemporary world situation.” ------- Alexandra Safronova, Chairperson, Institute of Asian and African Studies, Moscow State University, Moscow The book reflects upon the Russian Revolution of 1917 and the ensuing developments in Russia, the rest of the former Soviet Union, Central and Eastern Europe and elsewhere in the world. It discusses the impact of the legacies of the Russian Revolution on political systems, ideologies, economic and social structures and culture. The book answers some pertinent questions: To what extent are these legacies relevant today for the contextualisation of memory politics, social institutions, and international relations? How does an analysis of 1917 and its legacies contribute to the comparative study of revolutions and social change? Anuradha M. Chenoy is a Professor and former Dean of School of International Studies, Jawaharlal Nehru University, New Delhi, India. Archana Upadhyay is a Professor in the Centre for Russian & Central Asian Studies, School of International Studies, Jawaharlal Nehru University, New Delhi, India. .